2013
DOI: 10.1021/ja411631v
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Amide Directed Assembly of a Diastereo- and Enantiopure Supramolecular Host and its Application to Enantioselective Catalysis of Neutral Substrates

Abstract: The synthesis of a novel supramolecular tetrahedral assembly of K12Ga4L6 stoichiometry is reported. The newly designed chiral ligand exhibits high diastereoselective control during cluster formation, leading exclusively to a single diastereomer of the desired host. This new assembly also exhibits high stability toward oxidation or a low pH environment and is a more robust and efficient catalyst for asymmetric organic transformations of neutral substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
131
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(138 citation statements)
references
References 34 publications
0
131
0
6
Order By: Relevance
“…1 and 2A) (33,34). Assembly 1 exhibits 12 intramolecular amide hydrogen bonds which, in analogy to structurally important peptide bonds found in polypeptides, preferentially stabilize the desired tetrahedral supramolecular structure over other conformers (35).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1 and 2A) (33,34). Assembly 1 exhibits 12 intramolecular amide hydrogen bonds which, in analogy to structurally important peptide bonds found in polypeptides, preferentially stabilize the desired tetrahedral supramolecular structure over other conformers (35).…”
mentioning
confidence: 97%
“…Assembly 1 exhibits 12 intramolecular amide hydrogen bonds which, in analogy to structurally important peptide bonds found in polypeptides, preferentially stabilize the desired tetrahedral supramolecular structure over other conformers (35). Compound 1 and related hosts have been shown to catalyze several important chemical reactions with sizable rate accelerations (up to 10 6 ) and unusual selectivity reminiscent of enzyme catalysis (34,(36)(37)(38)(39)(40)(41). Unlike most enzymes, the reactions catalyzed by 1 are functionally and mechanistically very diverse.…”
mentioning
confidence: 99%
“…When the chiral amine subcomponent was displaced by the achiral amine tris(2-aminoethyl)amine, the cage retained its stereochemistry with high enantiomer excess (99%ee) (Figure 12) [71]. Raymond et al reported the diastereoselective formation of a tetrahedral cage assembled using six biscatecholates with chiral amide terminals and four Ga(III) cations without involving any cationic species [72]. The chiral cage possessed greater stability toward air oxidation and low pH compared to the corresponding tetrahedral cage without chiral amide terminals.…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 99%
“…At the present stage, various types of luminescent lanthanide complexes have been reported [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Luminescent lanthanide coordination polymers as the thermostable luminescent materials have recently been studied.…”
Section: Introductionmentioning
confidence: 96%